Conserving agricultural biodiversity - Verma, Saundaram (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Research on chills and agroforestry that received the 'Using Diversity Award' from the International Development Research Centre (IDRC), Canada, is briefly presented.